2018
DOI: 10.1152/ajpgi.00044.2018
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle intervention for morbid obesity: effects on liver steatosis, inflammation, and fibrosis

Abstract: The prevalence of obesity-related nonalcoholic fatty liver disease (NAFLD) is rising. NAFLD may result in nonalcoholic steatohepatitis (NASH), progressing to liver cirrhosis. Weight loss is recommended to treat obesity-related NASH. Lifestyle intervention may improve NASH; however, pertinent trials have so far focused on overweight patients, whereas patients with obesity are at highest risk of developing NAFLD. Furthermore, reports of effects on liver fibrosis are scarce. We evaluated the effect of lifestyle i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 34 publications
1
32
0
11
Order By: Relevance
“…In the trial by Hohenester et al, a weight loss of more than 10% showed a significant decline of ALT serum levels and an improvement of hepatic steatosis. In contrast, weight loss <10% was overall less significantly efficient in order to achieve a 'complete hepatic response' (normal serum ALT values, improved FLI and NFS) at week 52 [3].…”
Section: Studies On Dietary Interventionsmentioning
confidence: 86%
See 1 more Smart Citation
“…In the trial by Hohenester et al, a weight loss of more than 10% showed a significant decline of ALT serum levels and an improvement of hepatic steatosis. In contrast, weight loss <10% was overall less significantly efficient in order to achieve a 'complete hepatic response' (normal serum ALT values, improved FLI and NFS) at week 52 [3].…”
Section: Studies On Dietary Interventionsmentioning
confidence: 86%
“…Thus, further studies, that use less resources could be important in the management of NASH. In a monocentric, single arm, interventional study by Hohenester et al, the effects of a formula diet on hepatic steatosis and fibrosis were determined in patients with morbid obesity in Germany [3]. The intervention consisted of calorie restriction to 800 kcal/day for 12 weeks, with a follow-up of 13 weeks on a normal, balanced meal.…”
Section: Studies On Dietary Interventionsmentioning
confidence: 99%
“…It is well known that obesity or metabolic syndrome per see can be a significant risk factor of liver fibrosis. 43 Even though all non-NASH subjects exhibited normal liver function values, we have to be careful when dealing with the obtained results. Ideally, MMP-1 expression should be analyzed and compared between patients with NASH and simple steatosis without any inflammation or fibrosis, both of which are diagnosed by liver biopsy.…”
Section: Dovepressmentioning
confidence: 99%
“…Weight loss of 5% via caloric restriction has been shown to improve steatosis, weight loss of 5% to 7% resulted in improved inflammation, and a 7%-10% reduction in weight led to possible NAFLD/NASH remission and improved fibrosis[ 51 ]. Investigation by Hohenester et al [ 52 ], found that 11.8% of patients demonstrated liver fibrosis at baseline via NAFLD fibrosis score. Following weight loss, 0% of patients were fibrotic after 52 wk ( P < 0.05).…”
Section: Introductionmentioning
confidence: 99%